PROFILE OF MATHEMATICS LEARNING MEASUREMENT MATERIAL FOR SCAVENGER CHILDREN AT "SEKOLAH KAMI" BEKASI - Nur Azizah Imaroh; Sukirwan Sukirwan; Cecep Anwar Hadi Firdos Santosa (Delta: Jurnal Ilmiah Pendidikan Matematika, 2023)
This study aims to describe the mathematics learning profile of scavenger children in the "Our School" study group, to determine the scavenger children's learning interest and motivation in our school. Researchers used qualitative research with the snowball sampling method, there were 5 informants. This research is supported by a descriptive approach. Data collection in this study was obtained from observation, interviews, and documentation. The research results obtained are generally related to learning mathematics for students of the 4th grade equivalent of elementary school at "Sekolah Kami" who are very enthusiastic about learning mathematics, although they still need explanations slowly and repeatedly so that students can follow the lesson well. The mathematics competence mastered by the 4th grade students of SD Sekolah Kami in measurement material is quite masterful, even though when it is reviewed, it still has to be reminded occasionally with a clue. For the interest and motivation to study during the research the students were quite high but to do their homework they often did not do it at home because they also received less guidance from their parents, so that the opportunity to study and do assignments at home was not used.